The association of long-term ambient fine particulate matter exposure with blood pressure among Chinese adults. (1st January 2023) - Lin, Zhennan; Chen, Shufeng; Liu, Fangchao; Li, Jianxin; Cao, Jie; Huang, Keyong; Liang, Fengchao; Chen, Jichun; Li, Hongfan; Huang, Jianfeng; Hu, Dongsheng; Shen, Chong; et al.
Abstract: Previous studies indicated that long-term exposure to high level of fine particulate matter (PM2.5 ) was associated with elevated blood pressure (BP) and hypertension, but most of them were conducted in high-income countries with low PM2.5 level. Therefore, we aimed to evaluate the adverse impacts of long-term exposure to PM2.5 on BP and hypertension in China with high concentration. A total of 99, 084 adults aged ≥18 years old were included from three cohorts among the project of Prediction for Atherosclerotic Cardiovascular Disease Risk in China. PM2.5 concentrations during 2000–2015 at 1 × 1 km spatial resolution were evaluated using satellite-based spatiotemporal models. Generalized estimating equation was applied to assess the impact of three-year average PM2.5 concentrations on BP level and hypertension. We also examined whether health status and lifestyles modified the effects of PM2.5 on BP and hypertension. Generally, high concentration of PM2.5 was associated with increased BP level and higher risk of hypertension. With each 10 μg/m 3 increment in PM2.5 concentration, systolic BP (SBP) and diastolic BP (DBP) increased by 1.67 [95% confidence interval (CI): 1.48, 1.86] mmHg and 0.45 (95% CI: 0.35, 0.56) mmHg, and the prevalence of hypertension increased by 29% [odds ratio (OR): 1.29, 95% CI: 1.26, 1.32]. In comparison with the first quartile of PM2.5 concentration, SBP, DBP and prevalence of hypertension in the fourth quartile were increased by 8.26 (95% CI: 7.73, 8.80) mmHg, 2.85 (95% CI: 2.55, 3.15) mmHg, and 133% (OR: 2.33, 95% CI: 2.21, 2.47), respectively, in the fully adjusted model. However, the relationships of PM2.5 with BP might be non-linear, as BP level started to decline when PM2.5 exceeded 75 μg/m 3 . In conclusion, long-term PM2.5 exposure could elevate BP level and prevalence of hypertension. People living in high-polluted areas should strengthen their awareness of prevention. Graphical abstract: Image 1 Highlights: Fine particulate matter exposure increases blood pressure and hypertension risk. Effects of fine particulate matter on blood pressure differ from high-income areas. Non-linear relationship of fine particulate matter with systolic blood pressure.